Assessment of bowel vascularity using indocyanine green fluorescence in incarcerated hernia - Ganguly, Abhishek; Acharya, Abhijith; Pai, Manohar V.; Augustine, Alfred J. (International Surgery Journal, 2021)
Intra-operative assessment of bowel vascularity is often needed during emergent surgery. An objective test to determine the viability could reduce postoperative ischemic complications. Indocyanine green dye has been used for assessing bowel vascularity in colorectal surgery. The following study involving two patients demonstrates its use for assessing the viability of bowel in obstructed hernias after intraoperative intravenous injection. Stryker 1588 AIM laparoscopic setup was used for intraoperative fluorescence. In both cases, dusky areas were noted over the obstructed bowel segment on visual inspection. However, satisfactory fluorescence was seen after dye injection, and hence mesh repair was done without resecting the bowel. All the patients had a good post-operative recovery. Indocyanine green fluorescence may be a good modality to intraoperatively assess bowel vascularity.